2003
DOI: 10.1029/138gm10
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the Izu-Bonin-Mariana subduction factory

Abstract: The Izu-Bonin-Mariana (IBM) arc system extends 2800km from near Tokyo, Japan to Guam and is an outstanding example of an intra-oceanic convergent margin (IOCM). Inputs from sub-arc crust are minimized at IOCMs and mantle-to-crust fluxes can be more confidently assessed than for arcs built on continental crust. The history of the IBM IOCM since subduction began about 43 Ma may be better understood than for any other convergent margin. IBM subducts the oldest seafloor on the planet and is under strong extension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
329
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(336 citation statements)
references
References 238 publications
(337 reference statements)
3
329
1
3
Order By: Relevance
“…This appears to have contributed to horizontal flattening of the deep Izu-Bonin slab at depths near 550 km to the north of 28 • N (Lundgren and Giardini, 1994;Okal, 2001), versus the near vertical extension of the Mariana slab to depths of ∼800 km to the south of 20 • N (Faccenna et al, 2009;Stern et al, 2003;van der Hilst and Seno, 1993). At present, the trench is actually advancing toward the upper Philippine Sea Plate along the entire IBM arc, with clockwise rotation of the upper plate producing backarc extension along the Marianas.…”
Section: The Isolated 2015 Deep Eventmentioning
confidence: 98%
“…This appears to have contributed to horizontal flattening of the deep Izu-Bonin slab at depths near 550 km to the north of 28 • N (Lundgren and Giardini, 1994;Okal, 2001), versus the near vertical extension of the Mariana slab to depths of ∼800 km to the south of 20 • N (Faccenna et al, 2009;Stern et al, 2003;van der Hilst and Seno, 1993). At present, the trench is actually advancing toward the upper Philippine Sea Plate along the entire IBM arc, with clockwise rotation of the upper plate producing backarc extension along the Marianas.…”
Section: The Isolated 2015 Deep Eventmentioning
confidence: 98%
“…This relatively young onset of subduction in the south approximately coincides with the opening of the Mariana Trough back arc basin with rifting beginning sometime after 10 Ma and seafloor spreading beginning about 3 -4 Ma [Stern et al, 2003]. Moreover, the wide and rapid opening in the south is coupled with lengthening of the Challenger Deep segment in the E-W direction.…”
Section: Recent Reorganization Of Subduction Near the Challenger Deepmentioning
confidence: 99%
“…25.1). The present hydrothermal activity in the Mariana Trough is estimated to have started about 7 million years ago (Ma) (Stern et al 2003) and some dating studies reported records of mineralization in this region since 12,000 years ago (Stüben et al 1994;Takamasa et al 2013;Ishibashi et al Chap. 23).…”
Section: Introductionmentioning
confidence: 99%